PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING TOGETHER (LT) DENGAN MEDIA SITUS PERADABAN DUNIA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SEJARAH (PENELITIAN TINDAKAN KELAS PADA SISWA KELAS X IIS 3 SMA NEGERI 5 SURAKARTA TAHUN AJARAN 2015/2016) - Kurniawan, Bagus; Joebagio, Hermanu; Musadad, Akhmad Arif (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
The purpose of this research is to improve motivation and student learning outcomes in history object of class X IIS 3 SMAN 5 Surakarta academic year 2015/2016 through the application of cooperative learning method type Learning Together model with World Civilization Site media in history subject. This research is classroom action research. The experiement was conducted in twwo cycle, with each cycle consisting of planning, action, observation, and reflection. Subjects were students of X IIS 2 SMAN 5 Surakarta which is consisting 29 student, history teacher, and the teacher and learning. Techniques of data collection is by interview, observation, questionaires, tests and document analyzing. Test validity of data using the technique of triangulation method and triangulation sourch (data). Data analysis using comparative descriptive techniques and interactive analys. Research procedure is the spiral model (Planning, Acting, Observing and Reflecting). The result showed that; (1) the application of cooperative learning method type learning together model with world civilization site media can improve student motivation in history subject of class X IIS 3 SMAN 5 Surakarta academic year 2015/2016. It can be seen from the result of the percentage of achievement indicators in the questionnaire student motivation in history subject. The student motivation in history subject of precycle is 57.30% increase to 75.95% in the first cycle and increase to 84.46.02% in the second cycle. This acquistion has exceeded the target of 80 %; (2) the application of cooperative learning method learning together model with world civilization site media can improve student learning outcomes of class X IIS 3 SMAN 5 Surakarta academic year 2015/2016. It can be seen from the mastery of cognitive test score. The completeness of student learning outcomes in precycle amount to 55.17% increase to 74.86% in the first cycle and successfully increase in the second cycle into 89.65%. This acquistion has exceeded the target of 80 %. Based on the research finding and discussion, it can be concluded that Cooperative Learning method with the type of Learning Together by using World Civilization Site Media can increase the motivation and learning outcomes of students of X IIS 3 of SMAN 5 Surakarta.